FTIR data alginate of Punctaria latifolia - Poza, Ailen Melisa (2025)
APL alginate and its fractions were analyzed using Fourier Transformed Infrared Spectroscopy (FT-IR) and compared with a commercial alginate (Fluka®). resume los datos de FTIR del alginato de Punctaria latifolia.